An examination of hepatitis B virus reactivation of neurootologic diseases treated with steroids - UMENO, Yuta; SAKATA, Toshifumi; NISHI, Tatsuro; MAEHARA, Hiroki; SAWATSUBASHI, Motohiro (jibi to rinsho, 2021)
HBV-infected patients can suffer lethal consequences if HBV is reactivated through immunosuppressive medicine or chemotherapy and progresses to hepatitis B. We investigated HBV-related serum markers (HBs antigen, HBs antibody, HBc antibody) in patients with peripheral facial nerve paralysis and sudden deafness who received steroid therapies (total of 148 cases subjected to an HBs antigen analysis at the start of treatment). HBs antigen positivity was noted in none of the 148 cases (0 %); HBs antibody positivity was noted in 12 of 33 cases (36.4%), and HBc antibody positivity was noted in 7 of 25 cases (28.0%). No cases of reactivation of HBV or hepatitis B after steroid therapy were noted. Liver dysfunction developed in 2 of 8 patients (25.0%) who underwent regular post-treatment liver function testing. Forty-seven cases were treated with steroids for ≧ 2 weeks, and 101 were treated for < 2 weeks. Reactivation of HBV is thought to depend more on the duration of administration than on the dose of steroids, and the duration of treatment may need to exceed two weeks in order to ensure an adequate quantity of steroids has been administered for treatment. Therefore, when initiating steroid treatment, serum markers associated with HBV (HBs antigen, HBs antibody, HBc antibody) should be measured as an HBV screening analysis.